2016
DOI: 10.1108/9781786358820
|View full text |Cite
|
Sign up to set email alerts
|

Applied Structural Equation Modelling for Researchers and Practitioners

Abstract: No part of this book may be reproduced, stored in a retrieval system, transmitted in any form or by any means electronic, mechanical, photocopying, recording or otherwise without either the prior written permission of the publisher or a licence permitting restricted copying issued in the UK by The Copyright Licensing Agency and in the USA by The Copyright Clearance Center. Any opinions expressed in the chapters are those of the authors. Whilst Emerald makes every effort to ensure the quality and accuracy of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 0 publications
0
34
0
4
Order By: Relevance
“…Prior to CFA, two important assumptions should be met i.e. no outliers and normality (Byrne, 2016;Hair et al, 2010;Ramlall, 2016). Data screening detected and removed four outliers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to CFA, two important assumptions should be met i.e. no outliers and normality (Byrne, 2016;Hair et al, 2010;Ramlall, 2016). Data screening detected and removed four outliers.…”
Section: Resultsmentioning
confidence: 99%
“…Normality assessment was performed using the skewness and kurtosis indexes. Results revealed that absolute values of skew are smaller than 3.0, and absolute values of kurtosis are smaller than 7.0, suggesting a normal distribution of the dataset (Byrne, 2016;Kline, 2015;Ramlall, 2016). Subsequently, CFA was conducted to assess how well measurement variables reflect the latent constructs by examining convergent validity and discriminant validity (Hair et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, structural equation modeling (SEM) was utilized to evaluate the associations between SC, knowledge transfer, innovation, and organizational performance. Moreover, SEM is known to be able to deal with many dependent variables compared to regression technique, which usually has one dependent variable (Ramlall, 2016). In addition, this SEM technique has been applied by an increasing number of scholars from different fields, particularly in measuring the SC dimensions (Youssef, Haak-Saheem & Youssef, 2017;Fornell & Larcker, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Several other limitations must be also considered. First, the latent construct lacks direct measure and does not have inherent units (Ramlall, ). Therefore, the direct translation of our results to public health may be limited.…”
Section: Discussionmentioning
confidence: 99%